There is no one way to internationalization at home: Virtual mobility and student engagement through formal and informal approaches to curricula (Revista Lusófona de Educação, 2020)
Internationalization at Home (IaH) is the most accessible approach for internationalizing education, as it does not involve mobility or considerable investment. This article discusses the results of two distinct IaH initiatives: a 4-week collaboration between students from a Portuguese university and a Mexican university, and a set of activities conducted throughout one semester in a multicultural classroom in one Portuguese university. The analysis shows that, despite the clear differences between the two initiatives, they provided very interesting outcomes, with students recognizing the development of intercultural communication skills and other soft skills, which were perceived as adding value to the learning process and to their future professional careers.Keywords: internationalization of higher education; internationalization of the curricula; classroom collaboration; multicultural classroom.